PENGELOLAAN AIR TANAH DAN INTRUSI AIR LAUT - Herlambang, Arie; Indriatmoko, Robertus Haryoto (Jurnal Air Indonesia, 2005)
Coastal Aquifer System of Jakarta consist of unconfined aquifer layers, confined aquifer I and confined aquifer II. Resources of groundwater is very important for Jakarta City, for drinking water, industry, hotel, government offices and various other facility. Important considering of groundwater resources of Jakarta hence needed an effort to preserve the groundwater and awake its continuity by conducting a system management of groundwater. Model used for the management of groundwater system of aquifer coastal referred as Groundwater Model Simulation and Optimization of Quasi Three Dimension ( OPT-Q3D). Model simulation and optimization represent computer model of quasi-three dimensions with method of finite difference used for the operation of infiltration of sea water. This model can conduct current simulation of groundwater flow, head of fresh water and brine, and describe the movement of interface fresh water and sea water. The model can also make optimization of system aquifer with single or multi layers. Jakarta Groundwater Basin assumed consist three layers of aquifer separated by impermeable layer. Applying of groundwater simulation model in Jakarta can give information regarding balance of groundwater, head of freshwater, head of brine, interface brine and freshwater, map of brine distribution and bargain in each; every aquifer. Herein after model optimization will yield various information able to wear upon which consideration to manage the amount of pumping of optimal ground water every area in each layer of aquifer, amount of optimal pumping, optimal freshwater head, head of optimal brine and map of infiltration. Kata Kunci : Air Tanah, Pengelolaan, Intrusi Air Laut, Modeling